The role of anti-vascular endothelial growth factor (anti-VEGF) in the management of proliferative diabetic retinopathy - Yue Zhao; Rishi P Singh (BioExcel Publishing Ltd, 2018)
Diabetes is a major cause of visual impairment among workingage adults in the United States. The proliferative form of diabetic retinopathy is associated with severe vision loss (acuity <5/200). The standard treatment in proliferative diabetic retinopathy (PDR) is panretinal photocoagulation (PRP), which is effective but has established side effects such as peripheral visualfield constraints. Vascular endothelial growth factor (VEGF) is thought to drive the process of vascular proliferation. Drugs targeting VEGF (anti-VEGF) have been studied extensively in diabetic macular edema (DME), and results have shown that diabetic retinopathy regresses with anti-VEGF treatment. Recent studies show that anti-VEGF is not inferior to PRP for PDR while treatment is maintained, though recurrence rate when anti- VEGF treatment is stopped is unclear. In vitreous hemorrhage where PRP cannot be performed, use of anti-VEGF medications can treat underlying PDR and delay or reduce need for vitrectomy. Limitations of anti-VEGF treatment, however, require careful patient selection and monitoring. This review discusses recent clinical trials and guidelines for anti-VEGF use in PDR.